Persepsi Orang Tua Pada Sistem Zonasi Penerimaan Peserta Didik Baru: Studi Deskriptif di SMP Negeri 7 Jakarta - Wening Nurul Laily; Desy Safitri; Sujarwo Sujarwo (LPPM Universitas 17 Agustus 1945 Semarang, 2024)
This study aims to describe parents' perceptions of PPDB zoning systems and why parents care about PPDB zone systems. The research methods used in this study are descriptive methods with a quantitative approach. The population in this study is the parents of the students of the eighth grade of the State High School 7 Jakarta Teaching Year 2022/2023 who have been received through the zoning system with a sample of research of 55 samples with data collection techniques through lifts or questionnaires, surveys, library studies and documentation. The results of the research show that the perception of parents on the PPDB zoning system can be seen based on three aspects, namely the cognitive, affective and connative aspects. Data show that parents' perception in the cognitive aspects or parents' knowledge on the zoning systems in either category, on the affective aspect or feelings of parents indicate the perceptions of parents in the category of good and the connitive aspect or behavior of the parents of pupils of the eighth grade students in the 7th grade State High School in good category. Then, the reason parents care about the zoning system is for their children to have easy access to education and guarantee quality education due to the loss of favourite and unfavourite schools.